Pathophysiology of Cerebral Hyperperfusion in Term Neonates With Hypoxic-Ischemic Encephalopathy: A Systematic Review for Future Research - Kleuskens, Dianne G.; Gonçalves Costa, Filipe; Annink, Kim V.; van den Hoogen, Agnes; Alderliesten, Thomas; Groenendaal, Floris; Benders, Manon J. N.; Dudink, Jeroen (Frontiers in Pediatrics, 2021)
Worldwide neonatal hypoxic-ischemic encephalopathy (HIE) is a common cause of mortality and neurologic disability, despite the implementation of therapeutic hypothermia treatment. Advances toward new neuroprotective interventions have been limited by incomplete knowledge about secondary injurious processes such as cerebral hyperperfusion commonly observed during the first 1 to 5 days after asphyxia. Cerebral hyperperfusion is correlated with adverse neurodevelopmental outcome and it is a process that remains poorly understood. In order to provide an overview of the existing knowledge on the pathophysiology and highlight the gaps in current understanding of cerebral hyperperfusion in term animals and neonates with HIE, we performed a systematic research. We included papers scoping for study design, population, number of participants, study technique and relevant findings. Methodological quality was assessed using the checklist for cohort studies from The Joanna Briggs Institute. Out of 2690 results, 34 studies were included in the final review - all prospective cohort studies. There were 14 studies of high, 17 moderate and 3 of low methodological quality. Data from the literature were analyzed in two main subjects: 1) Hemodynamic Changes subdivided into macro- and microscopic hemodynamic changes, and 2) Endogenous Pathways which was subdivided into N-methyl-D-aspartate/Mitogen activated protein kinase (NDMA/MAPK), Nitric Oxide (NO), prostanoids and other endogenous studies. Cerebral hyperperfusion in term neonates with HIE was found to be present 10-30 minutes after the hypoxic-ischemic event and was still present around day 10 and up to 1 month after birth. Cerebral hyperperfusion was also characterized by angiogenesis and cerebral vasodilation. Additionally, cerebral vasodilation was mediated by endogenous pathways such as MAPK through urokinase Plasminogen Activator (uPA), by neuronal NO synthase following NMDA and by prostanoid synthesis. Future research should elucidate the precise role of NMDA, MAPK and prostanoids in cerebral hyperperfusion. Moreover, research should focus on possible interventions and the effect of hypothermia on hyperperfusion. These findings should be taken into account simultaneously with brain imagining techniques, becoming a valuable asset in assessing the impact in neurodevelopmental outcome.